Family Affective Functions and Temper Tantrums in Preschool Children: A Cross-Sectional Study: Fungsi Afektif Keluarga Dan Temper Tantrum Pada Anak Prasekolah: Studi Cross-Sectional - Kurniyawan, Enggal Hadi; Fitri, Lisca Nurmalika; Susumaningrum, Latifa Aini; Wuryaningsih, Emi Wuri; Susanto, Tantut (Al-Hijrah Indonesia, 2022)
Problems in the family can cause temper tantrum behavior in children. The effective function of the family aims to protect and provide psychosocial support for family members. This study aims to determine the relationship between family affective function and temper tantrum behavior in children. The research design is an analytic correlation with a cross-sectional study approach. Respondents in this study were 134 parents who had children aged 3-5 years. Sampling using a cluster sampling method. The questionnaires used in this study were the Family Affective Function Questionnaire and the Temper Tantrum Behavior Questionnaire. The parametric test in this study uses an independent sample t-test because the data is normally distributed. Temper tantrum behavior in children aged 3-5 years is screaming or screaming. Families with children aged 3-5 years can carry out family affective functions effectively. There is a relationship between family affective function and children's temper tantrum behavior with a p-value <0.001. Health education to parents with children aged 3-5 years about affective function must be carried out to prevent temper tantrums from occurring in childrens.